Optimizing the Capital Structure Using Cost of Capital Approach: a Case Study at PT.Telekomunikasi Indonesia, Tbk - Darsana, I Ketut Suwetja; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
PT Telekomunikasi Indonesia, Tbk (Telkom) keeps strengthening its infrastructure to support the business. Investment in infrastructure urgently needed as technologies always develop very fast following the services demanded. The fund for investment can be generated from internal cash flow, or generated from external sources from debt or equity. But it is important to consider the proper composition of funding to get the lowest cost of capital possible. The objective of this study is to examine Telkom’s optimal debt ratio, using cost of capital approach based on the condition as of December 31, 2012. Rating consideration, share repurchase program and high dividend are root causes that must be taken into consideration to maintain the company’s growth in the long run. A simulation applied to estimates the weighted cost of capital at different debt ratios. Some constraints, including debt rating and earnings before interest and tax (EBIT) volatility against debt ratio, are considered in order to reduce the risk of default. With current debt ratio of 14%, Telkom is still under levered. The optimum debt ratio is 17% after considering the constraints. Historical investments showed good performances with return on capital no less than 25%, which was higher than the current cost of capital of 9.31%. Considering the issuance cost, interest paid and macroeconomic conditions, it is recommended for the company to take new debt of Rp.7 trillions.  Keywords: capital, value, default, constraints. ehe @pr with BAPPENAS. Waste on Nambo TPPAS will be processed into useful products 1.Recycle Material 2. RDF(refuse derived fuel) 3. Compost. These projects are expected to be the solution to the waste problem in the city of Bogor and Depok. This Final Project is to analyze  the project feasibility study of development projects nambo TPPAS based on Regulation of Minister of national development planning No.3 2012 . Feasibility study perform by using various indicators of financial feasibility including IRR,NPV and PBP, combined with Sensitivity Analysis, Risk Analysis , and ABMS (analisa Biaya manfaat sosial – Social cost benefit Analysis). Based on the analysis of financial and risk positions suggests that development projects can be assessed Nambo TPPAS feasible to be implemented with the assumption that the government provide support in the form of government funding in the beginning of the project. However, the project can’t be assessed only in terms of financial side but must be assessed in terms of the resulting social benefits. These projects generate substantial EIRR. This prompted the government to immediately implement the construction of this project.  Keyword: Waste, Waste management, RDF , PPP , Project feasibility Study.